2013
DOI: 10.9735/0975-4423.5.1.173-180
|View full text |Cite
|
Sign up to set email alerts
|

CYTOGENETIC TOXICITY EFFECTS OF LOCAL PURSLANE (Portulaca oleracea) LEAF CRUDE EXTRACTS ON NORMAL AND CANCER CELL LINES in Vitro

Abstract: include cancers, and other health complains like respiratory, ophthalmological, dermatological, reproductive, and immunological complains [4]. It is widely held that (80-90%), of human cancers may be attributable to environmental, lifestyle factors such as tobacco, alcohol, and dietary habits [9,12]. Portulaca oleracea L. (Purslane) has been used as a kind of food and medicinal plant for thousands of years in China. P. oleracea is very important because of its special medical function and all its therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…They showed that the plant extract is non-toxic for normal cells and is safe for daily consumption (24). Some studies have shown that active constituents of P. oleracea ethanol extract have the cytotoxic, apoptotic, antiproliferative and cell cycle arrest properties against two AMN3 (Murine mammary adenocarcinoma) and RD (Rabdomyosarcoma) cancer cell lines after 24,48 and more efficiently 72 hours (25). It has been confirmed that after increasing the concentration of aqueous extract of P. oleracea to 100 µg /ml, more HEPG2 (liver hepatocellular carcinoma) cells faced death, and these results showed the cytotoxic effect of P. oleracea on this cell line (26).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the plant extract is non-toxic for normal cells and is safe for daily consumption (24). Some studies have shown that active constituents of P. oleracea ethanol extract have the cytotoxic, apoptotic, antiproliferative and cell cycle arrest properties against two AMN3 (Murine mammary adenocarcinoma) and RD (Rabdomyosarcoma) cancer cell lines after 24,48 and more efficiently 72 hours (25). It has been confirmed that after increasing the concentration of aqueous extract of P. oleracea to 100 µg /ml, more HEPG2 (liver hepatocellular carcinoma) cells faced death, and these results showed the cytotoxic effect of P. oleracea on this cell line (26).…”
Section: Discussionmentioning
confidence: 99%
“…The viability percentage was calculated with the following formula (7) :-%Growth Inhabition =absorbance of sample -absorbance of control / absorbance of control×100 Determination of IC50: A curve of percentage of viability cell versus concentrations was plotted from 5 replication of experiment. Inhibitory concentration (IC50), defined as concentration of the tested material that results in 50% of cell death, that was determined from the cell viability curve (8) Cell cycle analysis by flow cytometer : RD cells were treated with A. aspera ethanolic extract for 24, 48 and 72hours. The cells were harvested, washed, and fixed in 70% ethanol overnight at -20 C°, ethanol fixed cells were pelleted, washed ice-cold PBS, and resuspended in staining solution containing 50 µg/ml PI.…”
Section: Cell Viability Assaymentioning
confidence: 99%